Investigation of the Desalination Capacity of Activated Carbon Materials from Water Hyacinth (Eichhornia crassipes) Stems - Van Phuoc Nguyen; Dinh Duy Duong; Thi Tuu Tran; Huynh Cang Mai; Thi Kim Ngan Tran; Van Tan Lam; Long Giang Bach (Indonesian Journal of Chemistry, 2024)
To reduce the hazards brought by water hyacinth, many applications of water hyacinth have been studied and continuously expanded. The large biomass of water hyacinth is applied in many fields such as for wastewater treatment, wastewater purification, biological raw material sources, animal feed production, medicine, antioxidants, agriculture, and household appliances. This research investigates the desalination capacity of freshwater hyacinths, raw materials from water hyacinths, biochar, and activated carbon materials from water hyacinth stems. Results have shown that the suitable temperature for charring fresh water hyacinth is 420 °C. The activated carbon from the water hyacinth stems with a BET surface area of 200.4 ± 1.9 m²/g can be desalinated under the conditions of 0.4 g of activated carbon mass, 15 min of reaction time, 2.0 ppt of salt concentration, and at neutral pH. In contrast, raw materials from water hyacinths and biochar were unable to desalinate. This study evaluates the desalination ability of the activated carbon material of water hyacinth.